Atopic dermatitis in children. A current algorithm for the disease treatment and control - D. V. Proshutinskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article discusses key aspects of the pathogenesis of atopic dermatitis and issues of the selection of pathogenetically substantiated therapy methods. The authors provide data on the efficient use of basic drugs used to treat dermatosis in children - topical glucocorticosteroids and calcineurin inhibitors. The authors also describe a current algorithm for using topical calcineurin inhibitors during the period of an exacerbation of atopic dermatitis and to prevent relapses.